Pengaruh Kesulitan Keuangan, Ukuran Perusahaan, Likuiditas, dan Arus Kas Operasi terhadap Pengembalian Saham - Yurike, Yurike; Hermanto (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study aims to analyze the influence of factors such as financial distress (FD), firm size (SIZE), liquidity (CR), and operating cash flow (OCF) on stock returns in the food and beverage sub-sector industry listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The issue addressed relates to the importance of analyzing internal company factors in affecting stock returns, particularly in the consumer goods industry. The data used in this study is sourced from annual financial reports published by the companies, with a sample size of 40 data points from 8 companies selected through purposive sampling. In this study, data analysis was conducted using multiple linear regression methods via the STATA application. The findings of the study indicate that both financial distress and firm size have a significant impact on stock return performance. On the other hand, the variables of liquidity and operating cash flow do not have a significant impact on the company's stock return.